LDIflare small fiber function in normal glucose tolerant subjects with and without hypertriglyceridemia. Issue 1 (16th January 2015) - Vas, Prashanth RJ; Sharma, Sanjeev; Rayman, Gerry
ABSTRACT Introduction: We explored determinants of small fiber function (SFF) in normoglycemic individuals to determine influence of metabolic parameters, including triglyceride (TG) levels. Methods: Dorsal foot SFF was assessed by the LDIflare method in 79 individuals without clinical neuropathy, including 43 controls (HC, <1.7 mmol/L), 17 with mild hypertriglyceridemia (MiTG, 1.7–2.25), and 19 with significant hypertriglyceridemia (HiTG, >2.25 mmol/L). Results: LDIflare was significantly smaller in HiTG compared with HC (4.4 ± 1.4 vs. 9.3 ± 2.9 cm2; P < 0.0001) and compared with the MiTG (4.4 ± 1.4 vs. 7.0 ± 2.1; P < 0.0001). Over all, an inverse correlation existed between LDIflare and age (−0.42; P < 0.0001), weight (r = −0.37; P = 0.004), body mass index (BMI) (−0.51; P < 0.0001), Log10 triglycerides (r = −0.66; P < 0.0001), total cholesterol (r = −0.26; P = 0.02), and TC/HDL ratio (r = −0.40; P = 0.002). In multivariate regression analysis, Log10 triglycerides (P < 0.0001) and age (P = 0.003) were the only independent predictors. Conclusions: There is an inverse correlation between small fiber function and triglycerides in normoglycemic individuals and abnormal SFF in normoglycemic hypertriglyceridemia. Larger prospective studies are required to confirm these findings and to determine whether reduced SFF heralds later clinical neuropathy. Muscle Nerve52: 113–119, 2015